B07 Identification of protein interaction partners for kynurenine 3-monooxygenase, a candidate therapeutic target for Huntington's disease. (16th November 2010) - Thevandavakkam, M; Fleming, L M; Mason, R; Fleming Outeiro, T; Giorgini, F
Abstract : Metabolites of the kynurenine pathway (KP) of tryptophan degradation have been implicated in the pathophysiology of Huntington's disease (HD). In current and past studies we have found that inhibition of KMO is protective in several models of HD. KMO is a FAD dependent outer mitochondrial membrane enzyme that catalyses the conversion of L-kynurenine to the neurotoxic metabolite 3-hydroxykynurenine. In the central nervous system KMO is specifically expressed in microglia. In the present study we seek to further elucidate the biological role(s) of KMO in the cell. We have developed and optimised a novel version of the membrane split ubiquitin yeast two hybrid system (MbYTH) which permits identification of protein interaction partners of outer mitochondrial membrane proteins. This new technology has allowed us to perform two pilot screens to identify protein interaction partners of both human and yeast KMO. The protein interaction partners of KMO identified by MbYTH are involved in several cellular functions, including microtubule formation, synaptic vesicle trafficking, apoptosis, carbohydrate metabolism and energy homeostasis. Provocatively, KMO interacting proteins include proteins that interact with huntingtin, as well as proteins implicated neurodegeneration.